Feasibility Parameters of Rukyatulhilal Venue at Iqra' Tower of Universitas Muhammadiyah Makassar - Alamsyah Alamsyah; Yakub Yakub; Achmad Musyahid; Andi Ariiqah (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2023)
Observation of the new moon (Rukyatulhilal) is very dependent on sky conditions, views and location. The problem that is often encountered in the implementation of failed hilal (rukyat) observations is the condition of the rukyat field which cannot be separated from the influence of geographical location, atmosphere, pollution, and weather disturbances in the sky. This study aims to determine the feasibility of the Unismuh Makassar Iqra' Tower as a venue for Rukyatulhilal from the aspects of geographical location, pollution and weather disturbances in the field. The research method was divided into three stages: 1) Geographical observations include: location height, distance from the horizon, latitude and longitude of the place; 2) rukyat method (viewing the new moon directly using binoculars); 3) qualitative descriptive data analysis. The results of the study obtained data on the feasibility of the rukyat site, in accordance with the decision of the Supreme Court of the Republic of Indonesia concerning the feasibility of the rukyatulhilal location, namely the view in that direction should not be distracted, so that the horizon will look straight in areas that have an azimuth of 240° to 300°. However, Iqra' Tower of Unismuh Makassar with the view on the horizon is not disturbed by buildings so that the horizon will be seen straight with an azimuth of 269° 28' 42.06" The viewing height is 130.9 m, pollution and weather conditions are at a moderate level because it is not in the factory location. Therefore, the Iqra' tower is very representative as a place for the sighting of the new moon.